Prevalence of overweight and obesity in adult rural population of the northern part of Bačka and Banat - Pavlica Tatjana; Božić-Krstić Verica; Rakić Rada; Sakač Dejan (Vojnosanitetski Pregled)
Background/Aim. Obesity represents one of the frequent health problems in developed countries today. It is related to cardiovascular diseases, diabetes and various cancer forms. The aim of the study was to determine the prevalence of overweight and obesity in adult population of the northern Bačka and Banat. Methods. On the basis of a multistage stratified random sampling, 4,505 individuals of the age 40.61 ± 11.29 years took part in the study. The study included 46 rural settlements. The overweight and obesity prevalence was obtained using the anthropometric indicators of body mass index (BMI), waist circumference (WC) and the waist to hip ratio (WHR). The correlations among BMI, WC and WHR were determined by the Pearson's correlation coefficient while the multiple regression analysis was used for correlating sociodemographic parameters and the obesity index. Results. A significant positive correlation was found in relation to all anthropometric parameters in both sexes. The data indicated that 66.32% of males and 49.68% of females had an overweight problem. On average, approximately 38.52% of subjects of both sexes were overweight, while 19.48% were obese. The factors that largely contributed to higher values of the obesity index were the age of male subjects and the age, education and origin in females. Ragarding the female subjects, the level of education negatively correlated with the level of nutritional condition. Conclusion. The prevalence values of the overweight and obese subjects, obtained on the basis of the anthropometric parameters, vary. However, regardless methods applied, the percentage of the overweight and obese persons is very high, being among the highest recorded in European populations. The obtained results indicate the necessity of introducing better education programmes and conducting regular health controls among citizens in these regions.